Strategi Pengelolaan Dana Program Pengabdian Masyarakat: Perspektif Manajemen Keuangan Publik - Lase, Luther Hasan; Ristanto, Ristanto; Purwandaningsih, Sintya; Murodi, Ahmad (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
This study aims to analyze fund management strategies in community service programs through the perspective of public financial management (PFM). The focus of the study is directed at budget planning, distribution mechanisms, and financial control and accountability that support program effectiveness. The research method used is a qualitative approach with a case study design, involving in-depth interviews, financial document reviews, and observations at several community service organizing institutions. The results show that the application of PFM principles especially transparency, participation, and performance-based supervision can improve the efficiency of fund allocation, minimize the risk of abuse, and strengthen public accountability. In addition, the synergy between participatory planning and digital monitoring systems has been proven to speed up the reporting process and increase stakeholder trust. These findings confirm the importance of integrating PFM practices in the management of community service program funds to ensure sustainability and optimal social impact.ABSTRAKPenelitian ini bertujuan menganalisis strategi pengelolaan dana pada program pengabdian kepada masyarakat melalui perspektif public financial management (PFM). Fokus kajian diarahkan pada perencanaan anggaran, mekanisme distribusi, serta pengendalian dan akuntabilitas keuangan yang mendukung efektivitas program. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan desain studi kasus, melibatkan wawancara mendalam, telaah dokumen keuangan, dan observasi pada beberapa lembaga penyelenggara pengabdian masyarakat. Hasil penelitian menunjukkan bahwa penerapan prinsip PFM terutama transparansi, partisipasi, dan pengawasan berbasis kinerja mampu meningkatkan efisiensi alokasi dana, meminimalkan risiko penyalahgunaan, dan memperkuat akuntabilitas publik. Selain itu, sinergi antara perencanaan partisipatif dan sistem monitoring digital terbukti mempercepat proses pelaporan serta meningkatkan kepercayaan pemangku kepentingan. Temuan ini menegaskan pentingnya integrasi praktik PFM dalam pengelolaan dana program pengabdian kepada masyarakat untuk memastikan keberlanjutan dan dampak sosial yang optimal.